The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00253-016-8001-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygenation on the performance of three non-Saccharomyces yeasts in co-fermentation with Saccharomyces cerevisiae

Abstract: The sequential or co-inoculation of grape must with non-Saccharomyces yeast species and Saccharomyces cerevisiae wine yeast strains has recently become a common practice in winemaking. The procedure intends to enhance unique aroma and flavor profiles of wine. The extent of the impact of non-Saccharomyces strains depends on their ability to produce biomass and to remain metabolically active for a sufficiently long period. However, mixed-culture wine fermentations tend to become rapidly dominated by S. cerevisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 27 publications
8
58
3
Order By: Relevance
“…Oxygenation resulted in a general decrease in ethyl esters and acetates, particularly in ethyl butanoate, ethyl hexanoate, ethyl octanoate, ethyl decanoate and isoamyl acetate. These results are in agreement with those of other studies showing that reduced oxygen availability enhanced the production of desirable flavour compounds such as acetate and esters . In the case of ethyl esters this appears to be linked to yeast metabolism of unsaturated fatty acids, which are important constituents of cell membranes.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Oxygenation resulted in a general decrease in ethyl esters and acetates, particularly in ethyl butanoate, ethyl hexanoate, ethyl octanoate, ethyl decanoate and isoamyl acetate. These results are in agreement with those of other studies showing that reduced oxygen availability enhanced the production of desirable flavour compounds such as acetate and esters . In the case of ethyl esters this appears to be linked to yeast metabolism of unsaturated fatty acids, which are important constituents of cell membranes.…”
Section: Resultssupporting
confidence: 92%
“…While the impact of oxygen on fermentation efficiency has been widely studied, the potential effect of oxygen exposure during fermentation on the phenolic and aromatic characteristics of finished red wine has not been as thoroughly investigated, although cap management operations involve supply of variable amounts of oxygen. It is known that fermentation of musts in anaerobic condition can help increase yeast production of various esters contributing to wine fruity aromas in white wines . In red wine, it has also been shown that oxygen supply during fermentation can decrease the final concentration of certain volatile sulfur compounds …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the use of multi-strain starter cultures designed with autochthonous microbial resources (e.g. non-Saccharomyces yeasts combined with S. cerevisiae in controlled mixed fermentations), mimicking the natural diversity associated with spontaneous fermentation, can be recommended to improve wine (Comitini et al, 2011;Ciani & Comitini, 2015;Campbell-Sills et al, 2016;Shekhawat et al, 2017). In this regard, the non-Saccharomyces species, Torulaspora delbrueckii, Metschnikowia pulcherrima, Candida zemplinina and Hanseniaspora uvarum, are cited and intensively investigated the most (Comitini et al, 2011;Medina et al, 2012;Masneuf-Pomarede et al, 2015;Petruzzi et al, 2017a), while strains belonging to the species Lachancea thermotolerans, Metschnikowia fructicola, Schizosaccharomyces pombe, T. delbrueckii, Kluyveromyces thermotolerans, Pichia kluyveri and M. pulcherrima are already commercialised Petruzzi et al, 2017a).…”
Section: Product Innovationmentioning
confidence: 99%
“…In other studies, the population ratios and concentrations were determined offline by counting colony forming units on agar plates. This is either enabled by the use of selective antibiotics (Brou, Taillandier, Beaufort, & Brandam, 2018;Shimizu, Mizuguchi, Tanaka, & Shioya, 1999;Taniguchi et al, 1998) or the individual colonies were assigned to each species by different morphologies (Shekhawat, Bauer, & Setati, 2017). Another option is given by genetically introducing different fluorescence tags into each strain, allowing species-specific cell counting by flow cytometry (Spacova et al, 2018).…”
mentioning
confidence: 99%